Adaptive emotion regulation mediates the relationship between self‐compassion and depression in individuals with unipolar depression. (15th October 2016) - Diedrich, Alice; Burger, Julian; Kirchner, Mareike; Berking, Matthias
Abstract : Objectives: To identify the mechanisms involved in the association between self‐compassion and depression, we examined whether adaptive emotion regulation would mediate the relationship between self‐compassion and depression in individuals with unipolar depression. Furthermore, we explored which specific emotion regulation skills would be most important in this relationship. Design and method: Sixty‐nine individuals with unipolar depression were assessed with the Self‐Compassion Scale and the Emotion Regulation Skills Questionnaire at baseline and with the Beck Depression Inventory‐II 1 week later. Results: The results showed that successful application of emotion regulation skills mediates the association between self‐compassion and depression. Among eight specific emotion regulation skills, only the ability to tolerate negative emotions was identified as a significant mediator in the self‐compassion–depression relationship. Conclusions: These findings provide preliminary evidence that systematically fostering self‐compassion might help depressed individuals cope with their symptoms by enhancing their abilities to tolerate undesired emotions. Practitioner points: Systematically fostering self‐compassion through specific compassion‐focused interventions might facilitate a reduction in depressive symptoms by improving the person's emotion regulation abilities, especially by improving his or her ability to tolerate negative emotions. Hence, compassion‐focused interventions might be particularly promising in depressed patients with a tendency to avoid negative emotions and deficits in tolerating them.